Pendampingan perancangan smart botanical garden pada pelajar Kota Medan - Ertina Sabarita Barus; Christin Erniati Panjaitan; Winner Nainggolan; Muhammad Irwanto; Dewi Sholeha; Togar Timoteus Gultom; Muhammad Ikhwan Fahmi; Amani Darma Tarigan; Denny Hasminta S. Maha (SELAPARANG: Jurnal Pengabdian Masyarakat Berkemajuan, 2026)
Abstrak Pendampingan ini diberikan dikarenakan minimnya pengajar di sekolah yang memahami robotik dan sarana yang kurang mendukung. Sehingga pendampingan ini diperlukan karena minimnya pengetahuan para pelajar dalam merakit robot. Pendampingan perancangan ini diberikan kepada siswa-siswa kota Medan untuk mengenalkan konsep dasar elektronika sehingga pelajar tersebut semakin tertarik tentang robotika. Pendampingan ini diberikan oleh staff Teknik Elektro UNPRI. Peserta yang hadir dari jenjang SD, SMP dan SMA dengan total 70 orang. Dalam pendampingan ini siswa akan diberikan motivasi dan materi merakit robot Smart Botanical Garden. Lalu siswa akan dipecah berdasarkan kelompok jenjang pendidikan. Adapun tingkat kesulitan setiap kelompok akan disesuaikan dengan jenjang pendidikannya. Setiap kelompok akan dipersiapkan dengan komponen robot. Dan layout disediakan untuk tempat testing dan running hasil rakitan. Hasil pendampingan ini adalah siswa-siswa semakin memahami komponen dan fungsinya dan selektif memilih komponen yang akan dipakai dalam perakitan. Kata kunci : pendampingan; robot; perakitan; komponen Abstract This support is rendered due to the deficiency of educators in schools knowledgeable in robotics and the insufficient infrastructure. Consequently, this mentorship is essential owing to the students' inadequate understanding of robot assembly. This design mentoring is offered to students in Medan to familiarize them with fundamental electrical ideas, consequently enhancing their interest in robots. This guidance is provided by the staff of the Electrical Engineering Department at UNPRI. The participants, numbering 70 individuals, represent elementary, middle, and high school levels. During this mentorship session, students will receive motivation and resources to construct the Smart Botanical Garden robot. The kids will thereafter be categorized into groups according to their educational levels. The challenge level for each group will be modified based on their educational attainment. Every group will receive robotic components. A layout will be supplied for the evaluation and execution of the combined outcomes. This coaching results in students gaining a deeper understanding of the components and their functions, enabling them to be discerning in their selection of components for assembly. Keywords: coaching; robot; assembly; components